Supersonic flow over low aspect-ratio wings - Richards, I. C. (Cranfield University, 1976)
An attempt has been made, by means of exp": rimental work, to consolidate and augment existing knowledge of high-speed flows over delta wings. Particular emphasis . is placed on the investigation of flows which did not confirm to the 'accepted' pattern. In Part 1 the flow regimes on a caret wing are discussed with particular emphasis placed on the occurrence of 'strong' oblique shocks. Results are presented which demonstrate that when viewed in direction normal to the leading edge, shocks of both the 'weak' and the 'strong' families can be said to exist. An experiment designed to produce a single strong shock by means of a caret wingýof large anhedral, instead gave rise to a complex multiple shock pattern which could not be adequately explained by exact inviscid theory. In Part 2 the unexpected pressure rises reported on the lee surfaces of various delta wings (References 22 and 23) are shown to be, at least in part, the result of interference from the model support and base-mounted instrumentation. The physical reason for the pressure rise is discussed. 'Correct' leeside pressure distributions are pre- sented for one of the models used in Reference 23 for angles of attack up to 50 degrees. In Part 3 the different flow regimes on delta wings are discussed together with the methods of defining the boundaries between them. The conjecture that thin shock-layer theory can be used to predict the on- set of leading-edge separation is carefully investigated by means of tunnel tests on a particular wing with triangular cross-section.